Evolution and Conceptual Foundations of Nonhospice Palliative Care. (October 2019) - Beasley, Amy M.; Bakitas, Marie A.; Ivankova, Nataliya; Shirey, Maria R.
The term nonhospice palliative care was developed to describe and differentiate palliative care that is delivered prior to the end of life. The purpose of this article is to better define and clarify this concept using Rodgers's evolutionary concept analysis method. Attributes of nonhospice palliative care include (a) patient- and family-centered care, (b) holistic care, (c) interdisciplinary team, (d) early intervention, (e) quality of life-enhancing, (f) advanced care planning, (g) any age of the patient, (h) at any stage in illness, (i) care coordination, (j) concurrent curative treatment options, and (k) provided by primary and specialist providers. Nonhospice palliative care antecedents are serious illness, education, and access to services; consequences include benefits for the patient, family, provider, and health care system. Offering a clearly defined concept may allow for changes in health care to improve access to these services.